Willingness to pay for colorectal cancer screening: a comparison of elicitation formats - Frew, Emma J. (2003)
Willingness to pay is increasingly being used in health technology assessment, although a number of methodological issues remain unresolved. Using data collected from four studies, this thesis presents the findings from a direct comparison between alternative format designs to elicit willingness to pay for two alternative colorectal cancer screening tests; faecal occult blood (FOB) testing and flexible sigmoidoscopy (FS) testing. Along with the willingness to pay values estimated using the open-ended, payment scale, closed-ended and iterative bidding formats, information is collected on household income, attitudes toward health promotion and personal risk perceptions to determine the nature and value of responses. In comparison with the alternative formats, the closed-ended question design produced significantly higher WTP valuations and different justifications for those valuations. It is hypothesised that the yea-saying effect may explain this difference. The payment scale format achieved a higher completion rate compared to the open-ended design and both formats produced broadly similar valuations. Although a subsequent study suggested evidence of range bias within the payment scale design. The iterative bidding format produced higher valuations than the open-ended and payment scale but lower than the closed-ended, it is hypothesised that valuations obtained using different initial bids demonstrate the existence of starting point bias. Across all studies, respondents who have a high health motivation, are well educated, have a high household income and who are particularly worried about the disease have a positive effect on the willingness to pay for colorectal cancer screening.